Quest For Meaning Of Life In Charlotte Bronte's Novel Jane Eyre (1848): An Existentialist Criticism - Kurniawati, Rizky Indah (2012)
The research is proposed to analyze Quest for Meaning of Life in Jane Eyre novel by using Existentialist Criticism. It is done by establishing two objectives: the first is analyzing the movies based on its structural elements and the second is analyzing the movies based on the existentialist analysis The type of this research is descriptive qualitative. The object of the study is Jane Eyre novel written by Charlotte Bronte. There are two kinds of the data sources: primary and secondary. The primary data source is the novel itself and the secondary is other sources such as articles, essay, internet, encyclopedia, books of literary theory and other to support the subject matter. The method of collecting data is library research. The technique of data analysis is descriptive technique. Based on the analyses in the previous chapters, this study conveys to the following conclusions. First, based on structural analysis, it is evident that Charlotte Bronte conveys her idea that "Marrying someone who loves is better than marrying someone we love". Second, based on the existentialist criticism, it is apparent that in Jane Eyre, Charlotte Bronte wants to show an existentialist circumstance in which an individual encounters a situation that requires decision making.